P95 Molecular mechanisms of monocyte reprogramming in acute liver failure: importance of hepatically derived anti-inflammatory mediators. (6th September 2011) - Antoniades, C G; Zingarelli, V; Possamai, L; Mistry, R; Abeles, R D; Bruce, M; McPhail, M J W; Heaton, N; Auzinger, G; Bernal, W; Vergani, D; Thursz, M R; et al.
Abstract : Introduction: Monocytes from patients with acetaminophen-induced acute liver failure (AALF) bear striking phenotypic and functional similarities with endotoxin tolerant (ET) monocytes and may account for the marked predisposition to sepsis and increased mortality in AALF. ET reprograms monocyte responses in response to lipolysaccharide (LPS) stimulation by reducing expression of pro-inflammatory (eg, TNF-α, IL-6) and augmenting the production of anti-inflammatory cytokines (eg, IL-10). At a molecular level, reductions in positive regulators (eg, NF-kBp65) of toll-like receptor (TLR)-4 dependent signalling pathway typify ET. Soluble anti-inflammatory mediators, such as IL-10 and SLPI, exert negative regulation of TLR responses via STAT3 and NF-kBp65 dependent signalling pathways respectively. Aim: To delineate the molecular mechanisms and functional consequences of ET in AALF. Method: Following TLR-4 (LPS; 100 ng/ml), IFN-γ (10 ng/ml) and IL-10 (50 ng/ml) stimulation, phosphoflow technique was used to identify changes in regulators of TLR (NF-kBp65, MAPK p38), STAT-1 and STAT-3 signalling pathways in ex-vivo CD14+/CD33+ monocytes in eight AALF patients and 10 healthy volunteers (HC). Results expressed as MFI and ratio of activation (MFI following LPS/IFN-γ/IL-10 stimulation divided by baseline MFI [RPMI]). Serum TNF-α, IL-10 and SLPI were measured by ELISA (pg/ml) in 34 AALF patients and 15 healthy volunteers (HC). Regional levels of TNF-α, IL-10 and SLPI (portal vein [PV]), hepatic vein [HV]) were determined using in a further five AALF patients at time of liver transplantation (LT). Hepatic expression of TNF-α, IL-10 and SLPI (all pg/ml below) was determined using whole liver tissue homogenates from seven AALF explants and eight controls. Ex-vivo monocyte phagocytosis of FITC-labelled Escherichia coli was determined in five AALF and 10 healthy volunteers (HC) using FACS analysis. Results: In contrast to HC, TLR-4 stimulation markedly reduced NF-kBp65 expression, while MAPKp38 signal transduction responses remained similar to that of HC (Abstract P95 figures 1–2 ). Baseline STAT-3 expression was significantly elevated in AALF patients compared to HC whereas no differences in STAT-1 expression was detected (Abstract P95 figure 2 ). Increase in STAT-3 expression following IL-10 stimulation was similar between AALF patients and HC. AALF patients had significantly higher serum concentrations of TNF-α (21 vs 1.5; p<0.001), IL-10 (170 vs 40; p<0.001) and SLPI (71 200 vs 43 310; p<0.001) compared to HC. A trans-hepatic (HV > PV) gradient was seen for IL-10 and SLPI but not for TNF-α in 4 out 5 AALF patients sampled (Abstract P95 figure 3 ). Intra-hepatic levels of IL-10 (2 vs 0.6; p=0.03) and SLPI (442 vs 116; p=0.004) were higher in patients with AALF compared to controls, whereas no difference in TNF-α (24 vs 19; p=0.3) concentration was detected. The percentage of monocytes phagocytosing E coli was significantly reduced in ALF compared to HC (69 vs 92%; p=0.008). Conclusion: In AALF, circulating monocytes show modulations in intracellular signalling pathways compatible with ET and display reduced phagocytic capabilities. Our data also indicate that hepatic production of anti-inflammatory mediators, IL-10 and SLPI, may play a pivotal role in induction of ET monocytes and thus increase the risk of infection in AALF.